Abnormal transcranial Doppler cerebral blood flow velocity and blood pressure profiles in children with syndromic craniosynostosis and papilledema. Issue 4 (April 2016) - Spruijt, B.; Tasker, R.C.; Driessen, C.; Lequin, M.H.; van Veelen, M.L.C.; Mathijssen, I.M.J.; Joosten, K.F.M.
Abstract: Objective: Children with syndromic craniosynostosis are at risk of intracranial hypertension. This study aims to examine patient profiles of transcranial Doppler (TCD) cerebral blood flow velocity (CBFv) and systemic blood pressure (BP) in subjects with and without papilledema at the time of surgery, and subsequent effect of cranial vault expansion. Methods: Prospective study of patients treated at a national referral center. Patients underwent TCD of the middle cerebral artery 1 day before and 3 weeks after surgery. Measurements included mean CBFv, peak systolic velocity, and end diastolic velocity; age-corrected resistive index (RI) was calculated. Systemic BP was recorded. Papilledema was used to indicate intracranial hypertension. Results: Twelve patients (mean age 3.1 years, range 0.4–9.5) underwent TCD; 6 subjects had papilledema. Pre-operatively, patients with papilledema, in comparison to those without, had higher TCD values, RI, and BP (all p = 0.04); post-operatively, the distinction regarding BP remained (p = 0.04). There is a significant effect of time following vault surgery with a decrease in RI (p < 0.01). Conclusion: Patients with syndromic craniosynostosis who have papilledema have a different TCD profile with raised BP. Vault surgery results in increased CBFv and decrease in RI, however the associated systemic BP response to intracranial hypertension remained at short-term follow-up.